Information Base Security Threats and Challenges' in Information Forensic: A Survey - Dilip Kumar Barai; G. Sridevi; Syed Umar; MSR Prasad (Institute of Advanced Engineering and Science, 2016)
Generally to store the information or Information of any organization then they will be maintain Information base to manage that Information base we use some management techniques like Information base management systems so called DBMS. In this paper we introduced Relational DBMS which is a collection of applications that can store various information which can be easily retrieve, manipulate and storage of Information. So in this we are concentrating on forensic analysis and Information base of it which is very sensitive Information. In this paper we are analyzing and surveying of forensic Information based using various methodologies with different tools and algorithms for investigations, through which we got what are the challenges are facing in the forensic Information bases since the years.